Presbyterian Religion, Historiography, and Ulster Scots Identity, c. 1800 To 1914 - Holmes, Andrew R. (The historical journal, 2009)
The links between Presbyterians in Scotland and the north of Ireland are obvious but have been largely ignored by historians of the nineteenth century. This article addresses this gap by showing how Ulster Presbyterians considered their relationship with their Scottish co-religionists and how they used the interplay of religious and ethnic considerations this entailed to articulate an Ulster Scots identity. For Presbyterians in Ireland, their Scottish origins and identity represented a collection of ideas that could be deployed at certain times for specific reasons – theological orthodoxy, civil and religious liberty, and certain character traits such as hard work, courage, and soberness. Ideas about the Scottish identity of Presbyterianism were reawakened for a more general audience in the first half of the nineteenth century, during the campaign for religious reform and revival within the Irish church, and were expressed through a distinctive denominational historiography inaugurated by James Seaton Reid. The formulation of a coherent narrative of Presbyterian religion and the improvement of Ulster laid the religious foundations of a distinct Ulster Scots identity and its utilization by unionist opponents of Home Rule between 1885 and 1914.